Tingkat OTP (On Time Performance) Bandara Sultan Hasanuddin Makassar Tahun 2011 - Welly Pakan (Research and Development Agency of The Ministry of Transportation, 2012)
Air transportation is a mode of transportation at this time attracted many people because it has many advantages than other modes of transport, by 2011 this number of airlines operating in Indonesia there were 18 (eighteen) airlines that compete in the market and efforts to seize done is to give good service.One form of service from the airline is in the form of